Interdependent Self-Construal Masyarakat Kolektif dalam Novel “Laskar Pelangi” Karya Andrea Hirata (Kajian Psikologi Komunitas) - Jamilatul Baladiah; Rahmalia Rahmalia; Sherly Melinda Putri; Moh Lukman Hidatullah; Anisa Fajriana Oktasari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This article examines the concept of collectivism in Andrea Hirata's “Laskar Pelangi” novel by focusing on Interdependent Self-Construal. This study uses a qualitative method with data analysis focused on the dialogue between characters and the symbols contained in the novel. The results of this study indicate that the Laskar Pelangi novel reflects Interdependent Self-Construal in a collective society on Belitung Island. The people there prioritize common interests, a high sense of solidarity, and support each other in facing various challenges. This novel also describes a collective culture and shared values ​​that can shape the identity and behavior of individuals in a community. By focusing on Interdependent Self-Construal in a collective society, this study is expected to provide a deep understanding of the concept of Interdependent Self-Construal and inspire readers to understand the importance of collectivism in building a meaningful community.